EDUKASI KESIAPAN PEMERIKSAAN MANDIRI PENYAKIT HIV PADA KONSELOR PENJANGKAU KELOMPOK LELAKI SEKS LELAKI DI KOTA PADANG - Mahathir Mahathir; Bunga Permata Wenny; Rika Sabri; Agus Sri Banowo; Siti Yuliharni; Serly Berlian; Okky Adelirandy; Kintan Resqitha Ekaputri; T. Ramadhani (BULETIN ILMIAH NAGARI MEMBANGUN, 2022)
Men who have sex with sex men (MSM) recognized as key population, which is currently raising significant concern because of an increase number of HIV infection. The iceberg situation is a worrying situation that must be sought for an appropriate approach in order to protect this group from HIV infection. Improvement in HIV testing should be intensified, it is important to generate an effective strategy in order to increase HIV status notification among the group. HIV self-testing (HIVST) will essentially accommodate privacy, confidentiality and personal space for stigmatized key populations. This occasion was carried out by conducting focus group discussions with MSM HIV peer councelors of Akbar Foundation a non-governmental organization in Padang Indonesia by introducing HIV self-testing kit tools and tele counselling in HIVST program implementation. In November, a focus group discussion was held to discuss the possible strategies to be possibly implemented in the program. Participants said that the use of HIVST was not generally available as prevention options for key populations, especially MSM. Most participants agreed that having more free options for HIV testing would increase the rate at which will increase motivation to get to know their HIV status. However, concerns were also expressed about the accuracy of the test and the reliability of the results due to the lack of technical knowledge on how to conduct self-testing by the population. It is important to provide a HIVST program for MSM to increase the number of serostatus check among the group.